Perancangan Tempat Sampah Otomatis Berirama Menggunakan Sensor Ultrasonik Berbasis Mikrokontroler Atmega 328 di SD Negeri Wonosigro - Erman Al Hakim; Jati Sumarah; Nur Faizah Budi Mulyani (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2022)
Public awareness to dispose of garbage in its place is still considered low. It is evident that garbage is still scattered in public places so that a way is needed to increase public awareness. One way is to modify the trash can into an attractive trash can. A trash can that can automatically open and close and can bring up notifications and sounds. The research method uses Research and Development. The R&D stages include: collecting data, making product designs, building products, and testing products. The components of the tool include: ultrasonic sensor, ATmega 328 microcontroller, servo motor, I2C LCD, and speaker. The way the tool works is the ultrasonic sensor as an object detector, the ATmega 328 microcontroller as a processing tool. The output of the system is a servo motor as a trash can lid driver, LCD and speaker as notification. Based on the results of testing the entire system of Automatic Rhythmic Trash Can Design Using Ultrasonic Sensors Based on ATmega 328 Microcontroller, it is explained that ultrasonic sensors can detect objects with a distance of less than 50 cm.